2020
DOI: 10.1080/11745398.2020.1815068
|View full text |Cite
|
Sign up to set email alerts
|

Women’s outdoor adventure experiences on Instagram: exploring user-generated content

Abstract: Little is known about how everyday women self-present their outdoor adventure experiences, and how these compare to mainstream media, which often reinforces narratives of hegemonic masculinity. To better understand how everyday women portray their outdoor adventure experiences, we examine user-generated content on Instagram associated with the hashtags #womenoutdoors, #womeninadventure and #shewentwild. In total, 1154 posts were collected. Analysis revealed that Instagram facilitates a 'DigiPlace' that contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…(2020) showed that Instagram also allows for more diversity and empowerment of voices. In their research on the portrayal of women in the outdoors, they found that the posts on Instagram showed diverse ways of being outdoors, where women portrayed themselves as active participants, emphasizing ‘exploration, strength and courage, and “growing” through achievement and self‐fulfilment through overcoming challenges’ (Low et al., 2020, p. 19). Our participants were sensitive to these diverse voices, keen on including different perspectives in the people they followed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) showed that Instagram also allows for more diversity and empowerment of voices. In their research on the portrayal of women in the outdoors, they found that the posts on Instagram showed diverse ways of being outdoors, where women portrayed themselves as active participants, emphasizing ‘exploration, strength and courage, and “growing” through achievement and self‐fulfilment through overcoming challenges’ (Low et al., 2020, p. 19). Our participants were sensitive to these diverse voices, keen on including different perspectives in the people they followed.…”
Section: Discussionmentioning
confidence: 99%
“…However, Low et al (2020) showed that Instagram also allows for more diversity and empowerment of voices. In their research on the portrayal of women in the outdoors, they found that the posts on…”
Section: Aestheticization and Homogeneity Of Storiesmentioning
confidence: 99%
“…Outdoor activities are generally considered a male-dominant type of activities. However, the study revealed that some participants aimed to present a meticulous outdoor identity as an active participant and challenge the gendered and heteronormative perception of the society (Low, Miller, Doran & Hardwick, 2022). So, the social media is here used as a motivation to have a voice the field which is considered masculine.…”
Section: Technology Use In Outdoor Recreation As a Motivatormentioning
confidence: 99%